Struktur Frase dan Transformasi Bahasa Pada Puisi Aku Karya Chairil Anwar - Yustina Sako; Antonius Bere (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2023)
Phrase structure and transformation is a theory of generative transformation grammar which can produce or generate and change a certain linguistic form into another new linguistic form, which did not previously exist. Language consists of a deep layer and a surface layer. This theory separates language into two layers, namely deep structure and surface structure. Language analysis always starts from the sentences in the poem "AKU" by Chairil Anwar. The purpose of this research is to find out about the phrase structure and transformations in AKU poetry in the form of sentences and to analyze them based on transformation theory. The method used in this research is a quantitative descriptive method using reading and note-taking techniques in data collection techniques. The data analysis technique used is the agi method. The results of this research show that the sentences in the AKU poem undergo transformation and have a phrase structure in each sentence.